ANALISIS SEKUENS D-LOOP DNA MITOKONDRIA SAPI BALI DAN BANTENG DIBANDINGKAN DENGAN BANGSA SAPI LAIN DI DUNIA - DWINA WISESA, ANAK AGUNG NGURAH GEDE; KADE MAHARDIKA, I GUSTI NGURAH; OKA PEMAYUN, TJOK GEDE (Indonesia Medicus Veterinus, 2012)
The result of this study indicates the D-loop of mtDNA of bali cattle is homologous with banteng. Two haplotypes can be identified. The sequence is different from that of Bos taurus, Bos indicus, Bos javanicus, and Bos gaurus. Further research needs to be done with a representative sample for the entire population in Bali by targeting more than one locus. In addition, the effective population size of bali cattle needs to be known to improve the genetic quality of bali cattle.